Pericarditis with Atrial Septal Defect with Bilateral Haemorrhagic Ovarian Cyst: A Case Report - Salekin, Mohammad Serajus; Khan, Omar Sadeque; Urme, Sharmin Jahan; Adhikary, Asit Baran; Aftabuddin, Md (University Heart Journal, 2014)
We are reporting a case of bilateral haemorrhagic ovarian cyst with pericarditis with atrial septal defect (ASD) in a 32 years female. Diagnosis of ASD was incidental when she was under evaluation for bilateral haemorrhagic ovarian cyst. Diagnosis was confirmed by echocardiography. ASD was closed by Polytetrafluoroethylene (PTFE) patch. Pericardium was found full of multiple small whitish granular nodules. So pericardium was discarded as a patch. Pericardium was sent for histopathology and histopathology reveals chronic pericarditis. Postoperative course was uneventful with marked improvement of symptoms. DOI: http://dx.doi.org/10.3329/uhj.v9i1.19512 University Heart Journal Vol. 9, No. 1, January 2013; 52-53